2016
DOI: 10.1002/2016gc006296
|View full text |Cite
|
Sign up to set email alerts
|

Sources and turnover of organic carbon and methane in fjord and shelf sediments off northern Norway

Abstract: To better understand the present and past carbon cycling and transformation processes in methane-influenced fjord and shelf areas of northern Norway, we compared two sediment cores from the Hola trough and from Ullsfjorden. We investigated (1) the organic matter composition and sedimentological characteristics to study the sources of organic carbon (C org ) and the factors influencing C org burial, (2) pore water geochemistry to determine the contribution of organoclastic sulfate reduction and methanogenesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 104 publications
4
37
0
Order By: Relevance
“…Highest δ 13 C and highest contributions of marine origin organic matter (~80%) were found in two northern Norway fjords. Similar range of δ 13 C in Ullsfjord were also reported by Sauer et al () and interpreted as indicators of organic matter originating predominantly from marine phytoplankton. Relatively high photosynthetic pigments concentrations in Balsfjord sediments support the findings of Reigstad et al (), who showed that both in Balsfjord and Ullsfjord phytoplankton cells may dominate the vertical fluxes during bloom periods (as opposed to earlier suggestions of very strong zooplankton grazing and low sedimentation of fresh pelagic material to the sea bottom in northern Norwegian fjords).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Highest δ 13 C and highest contributions of marine origin organic matter (~80%) were found in two northern Norway fjords. Similar range of δ 13 C in Ullsfjord were also reported by Sauer et al () and interpreted as indicators of organic matter originating predominantly from marine phytoplankton. Relatively high photosynthetic pigments concentrations in Balsfjord sediments support the findings of Reigstad et al (), who showed that both in Balsfjord and Ullsfjord phytoplankton cells may dominate the vertical fluxes during bloom periods (as opposed to earlier suggestions of very strong zooplankton grazing and low sedimentation of fresh pelagic material to the sea bottom in northern Norwegian fjords).…”
Section: Discussionsupporting
confidence: 87%
“…The subarctic fjords located in northern Norway (Balsfjord and Ullsfjord) were characterized by much lower C org accumulation (and burial) rates, probably due to lower marine primary production and poorer terrestrial vegetation in this region. The low C org accumulation was also reported for Ullsfjord and adjacent Malagenfjord (Glud et al, 1998;Sauer et al, 2016).…”
Section: Organic Carbon Accumulation and Burialsupporting
confidence: 72%
“…It is a crossshelf trough with a width of 12km and water depth of around 200m (Sauer et al, 2016). Active methane seepage was documented by geophysical (Chand et al, 2008) and geochemical investigations (Sauer et al, 2015;Sauer et al, 2016). The sedimentation rate is relatively low and the organic matter in the sediments is predominately derived from terrestrial sources 10 (Sauer et al, 2016).…”
Section: Study Areamentioning
confidence: 99%
“…Active methane seepage was documented by geophysical (Chand et al, 2008) and geochemical investigations (Sauer et al, 2015;Sauer et al, 2016). The sedimentation rate is relatively low and the organic matter in the sediments is predominately derived from terrestrial sources 10 (Sauer et al, 2016). High flux of methane derived from the Late Jurassic and Early Cretaceous source rock (Sauer et al, 2015) results in rapid sulfate turnover through AOM as documented by porewater profiles (Sauer et al, 2016).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation